Storage-Induced Platelet Apoptosis Is a Potential Risk Factor for Alloimmunization Upon Platelet Transfusion - Saris, Anno; Peyron, Ivan; van der Meer, Pieter F.; Stuge, Tor B.; Zwaginga, Jaap Jan; van Ham, S. Marieke; ten Brinke, Anja (Frontiers in Immunology, 2018)
Platelet transfusion can elicit alloimmune responses leading to alloantibody formation against donor-specific polymorphic residues, ultimately resulting in platelet transfusion refractoriness. Universal leukoreduction significantly reduced the frequency of alloimmunization after platelet transfusion, thereby showing the importance of white blood cells (WBCs) in inducing this alloresponse. It is, however, unknown if the residual risk for alloimmunization is caused by WBCs remaining after leukoreduction or if alloimmunization can be induced by platelets themselves. This study investigated the capacity of platelets to induce alloimmunization and identified potential product-related risk factors for alloimmunization. First, internalization of allogeneic platelets by dendritic cells (DCs) was demonstrated by confocal microscopy. Second, after internalization, presentation of platelet-derived peptides was shown by mass spectrometry analysis of human leukocytes antigen (HLA)-DR eluted peptides. Third, platelet-loaded DCs induced platelet-specific CD4 T cell responses. Altogether, this indicates a platelet-specific ability to induce alloimmunization. Therefore, factors enhancing platelet internalization may be identified as risk factor for alloimmunization by platelet concentrates. To investigate if storage of platelets is such a risk factor, internalization of stored platelets was compared with fresh platelets and showed enhanced internalization of stored platelets. Storage-induced apoptosis and accompanied phosphatidylserine exposure seemed to be instrumental for this. Indeed, DCs pre-incubated with apoptotic platelets induced the strongest IFN-γ production by CD4 T cells compared with pre-incubation with untreated or activated platelets. In conclusion, this study shows the capacity of platelets to induce platelet-specific alloimmune responses. Furthermore, storage-induced apoptosis of platelets is identified as potential risk factor for alloimmunization after platelet transfusions.